MENGOPTIMALKAN PERKEMBANGAN KOGNITIF ANAK MELALUI KEGIATAN BERMAIN - Rohani Rohani (Universitas Islam Negeri Sumatera Utara, 2016)
Cognitive is a process of thinking is the ability of individuals to connect, assess and consider an incident or event. Associated with increased cognitive development of children's ability to think, solve problems, make decisions, intelligence and talent of children.Cognitive Aspects develops when children play is the child able to improve attention and concentration, is able to bring creativity, capable of divergent thinking, train memory, develop perspectives, and develop language skills.The game is one of the media learning fun for children. The game can stimulate cognitive development in children.